2015
DOI: 10.1113/ep085338
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metabolic and circulatory heterogeneity on the expression of pulmonary oxygen uptake kinetics in humans

Abstract: What is the main finding and its importance? 31Here we demonstrate how a first-order system can respond with non-first-order response 32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…However, it is becoming clearer (Hughson, ; Keir et al . ) that models that consider the complex interaction between O 2 delivery and utilization are more appropriate to study aerobic system dynamics. In fact, we showed that the overall ptrueV̇O2 dynamic is composed of a complex interaction between multiple‐order systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is becoming clearer (Hughson, ; Keir et al . ) that models that consider the complex interaction between O 2 delivery and utilization are more appropriate to study aerobic system dynamics. In fact, we showed that the overall ptrueV̇O2 dynamic is composed of a complex interaction between multiple‐order systems.…”
Section: Discussionmentioning
confidence: 99%
“…; Keir et al . ), absolute and relative standard error (SE and %SE, respectively) and the statistical significance level ( P ) of the estimated parameters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean response time ( MRT ) was calculated by adding t and TD (Macdonald et al, 1997). The quality of the fitting was assured by the analysis of squared error, coefficient of determination ( r 2 ), 95% confidence interval band ( CI 95 ) of the model (Fawkner et al, 2002; Keir et al, 2016) and the significance level ( p -value) of the estimated parameters. The comparison between MNG and τ, both derived from measured trueV˙O2 data, has the purpose to experimentally support the expected correlation between both parameters (further demonstrated by computer simulations).…”
Section: Methodsmentioning
confidence: 99%